THE ROLE OF EMPLOYEE WELL BEING IN ORGANIZATIONAL PERFORMANCE - Putro, Suryati Eko (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research aims to identify the main dimensions of employee well-being that influence organizational performance, using a systematic literature review (SLR) approach based on the PRISMA methodology. The research results show that psychological and social well-being have a significant impact on productivity, innovation and employee retention, while physical, career and financial dimensions of well-being also contribute to organizational performance. The implications of this research provide guidance for organizations in designing effective wellness programs to improve long-term business outcomes.